Industrial training report: My Fimedia Network Technology Sdn. Bhd. (Skintific Malaysia) - Mohd Ramli Alzaki, Siti Muyassarah Az-Zafirah (Faculty of Business and Management, 2025)
My most enticing and unforgettable six-month industrial training began here at My Fimedia Network Technology Sdn. Bhd. (SKINTIFIC), which equates to a duration of 24 weeks. My internship at Skintific Malaysia took place from 12th August 2024 until 24th January 2025. This report marks my completion of my Bachelor of Business Administration (Hons.) in Marketing at Universiti Teknologi Mara (UiTM) Bandaraya Melaka Campus. This report showcases the summary of my internship journey at Skintific Malaysia. It entails my primary responsibilities, accomplishment and knowledge gained during the internship program. This internship time was dedicated to acquiring hands-on industry experience and exposure in how the online marketing field works for famous brands in Malaysia. During my internship at Skintific Malaysia, my main duties were to handle comment operation tasks for all respected postings for the influences. In order to create a buzz about the brand, I was responsible for commenting on the postings regarding the products. Furthermore, I was also responsible for coming up with unique and catchy trigger text for new upcoming products for influences’ postings in TikTok. This report includes a SWOT analysis for Skintific Malaysia, as well as the suggestions and recommendations pertaining to the brand name. One of the qualities Skintific Malaysia possesses is their strong brand identity and diverse product range. That work in Skintific Malaysia alone has been extremely beneficial. The experience used a lot of what I taught in class about market research, product analysis, and other similar activities in the skincare industry, which was really interesting, as well as associated regulatory work. This internship has helped me strengthen my communication, critical thinking, and collaboration skills while also increasing my understanding of the brand's commitment to innovation, in other words, the internship helped me build vita! skills for personal and professional growth while I pursued a career in skincare and cosmetics.